Research progresses on target of rapamycin kinase in plants - CHEN Wenzhen; LIU Jiaqi; DU Hao (浙江大学学报. 农业与生命科学版)
In plants, target of rapamycin (TOR) functions as a pivotal signaling and metabolic hub, integrating nutrient availability, energy status, and environmental cues through phosphorylation. This regulatory mechanism plays a crucial role in governing plant growth, development, and environmental adaptation. In this paper, we provide a comprehensive review of the discovery and characterization of TOR in plants. We summarize previous and recent studies on the signaling pathway of plant TOR, highlighting the identification of upstream effect factors and downstream substrates. Additionally, we discuss the diverse roles of TOR in plant embryogenesis, meristem formation, nutrient utilization, flowering, senescence, and responses to both abiotic and biotic stresses. Furthermore, we explore the potential research prospects for TOR kinase and its application in agriculture.